Self-Es: The Role of Emails-to-Self in Personal Information Management - Bota, Horatiu; Bennett, Paul; Awadallah, Ahmed; Dumais, Susan (Proceedings of the 2nd ACM Conference on Human Information Interaction and Retrieval (CHIIR '17), 2017)
Email has been central to online communication for the past two decades. Through constant use, new information flows are being defined around users’ interactions with emails. Alongside traditional messages, the email inbox is an always available repository of to-do lists, reminders, files and notes. In this paper, we investigate the use of self-addressed emails (self-Es) as an information management tool, by analysing both: (i) responses to a survey about email use; and (ii) a collection of user donated self-addressed emails. Our results show that sending self-Es is a frequent behaviour among the users we questioned. In addition, we find that to-dos and reminders are the most popular type of information contained in emails-to-self. Our findings have direct implications for the development of systems that support novel interactions with information flows centered around email.